2022
DOI: 10.1371/journal.pmed.1004008
|View full text |Cite
|
Sign up to set email alerts
|

Digital solutions to promote adolescent mental health: Opportunities and challenges for research and practice

Abstract: Jason Bantjes discusses the accompanying study by Michelle Torok, Jin Han, and colleagues investigating the effects of a self-guided smartphone application on suicidal ideation among young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The scarcity of published research on this topic reflects the limited focus on adolescent mental health interventions in LMICs, despite increased mobile phone ownership and use in these countries (International Telecommunications Union [ITU], 2022). This also reflects that the field of MMH is a small but growing research area that dramatically increased due to the coronavirus pandemic, which required rapid advances in the use of MMH to deliver and ensure continuity of care (Bantjes, 2022). Nonetheless, the three domains identified provide insight into the perception and usefulness of MMH interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The scarcity of published research on this topic reflects the limited focus on adolescent mental health interventions in LMICs, despite increased mobile phone ownership and use in these countries (International Telecommunications Union [ITU], 2022). This also reflects that the field of MMH is a small but growing research area that dramatically increased due to the coronavirus pandemic, which required rapid advances in the use of MMH to deliver and ensure continuity of care (Bantjes, 2022). Nonetheless, the three domains identified provide insight into the perception and usefulness of MMH interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, Osman et al suggested that YouTube improve its ranking and recommendation system through giving higher weight to expert reviews of health-related videos and by including their assessment data in the ranking algorithm. Bantjes suggested that AI complement human-centered approaches to the promotion of adolescent mental health through facilitating therapeutic relationships, enhancing connectedness, and performing DMHI functions in combination with interventions provided by therapists [93]. However, to date, there are no scientific studies that have demonstrated AI helping people with mental health care.…”
Section: Future Researchmentioning
confidence: 99%
“…[1,2] Digital technologies are also a potentially cost-effective way to scale up access to mental healthcare, and there is emerging evidence that app-based interventions might be effective for suicide prevention among adolescents. [38] There is also evidence that some students in SA find digital mental health interventions acceptable and satisfying, [39] suggesting that digital technologies could be an effective way to deliver suicide prevention interventions to SA students, although more research is needed to verify whether these findings are generalisable to large groups of students in different settings. While digital interventions might be appealing (because they offer anonymity, convenience, access and affordability), there are significant problems associated with poor sustained engagement with digital interventions, which may make them unsuitable for use with high-risk groups, such as suicidal students.…”
Section: Researchmentioning
confidence: 99%